2018
DOI: 10.1124/jpet.118.249615
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Upregulates P-Glycoprotein in Human Caco-2 Cells and in an Experimental Model of Colitis in the Rat via Activation of Nrf2-Dependent Mechanisms

Abstract: Downregulation of P-glycoprotein (P-gp) is implicated in the pathophysiology of inflammatory bowel disease (IBD). Berberine, a principal isoquinoline alkaloid extracted from species, has been reported to exhibit therapeutic potential in IBD. In this study, we used a dextran sulfate sodium (DSS)-induced colitis rat model to evaluate the effect of berberine on P-gp and explore its mechanism of action. Berberine treatment improved DSS-induced colitis symptoms, attenuated inflammatory markers (myeloperoxidase, tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 55 publications
(77 reference statements)
1
24
0
Order By: Relevance
“…Our results are very similar to the finding that camptothecin (an isoquinoline alkaloid, like berberine) attenuates cytochrome P450 3A4 induction by blocking the activation of human PXR [23]. However, The results of this study are inconsistent with the recent data showing that berberine up-regulate P-gp through transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) but not through PXR when colitis occurs in rats [24]. This discrepancy is most likely due to the different regulatory pathways of P-gp between normal and pathologic systems.…”
Section: Discussionsupporting
confidence: 67%
“…Our results are very similar to the finding that camptothecin (an isoquinoline alkaloid, like berberine) attenuates cytochrome P450 3A4 induction by blocking the activation of human PXR [23]. However, The results of this study are inconsistent with the recent data showing that berberine up-regulate P-gp through transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) but not through PXR when colitis occurs in rats [24]. This discrepancy is most likely due to the different regulatory pathways of P-gp between normal and pathologic systems.…”
Section: Discussionsupporting
confidence: 67%
“…Isoquinoline alkaloids are classes of medicinally active alkaloids formed from a precursor of 3,4-dihydroxytyramine (dopamine) linked to an aldehyde or ketone with multiple properties including antispasmodic, antimicrobial, antitumor, antifungal, anti-inflammatory, cholagogue, hepatoprotective, antiviral, amebicidal, and anti-oxidant activities (Iranshahy et al, 2014). Berberine ( 7 ), a well-known representative of this type of alkaloid mainly isolated from traditional Chinese medicines Coptis chinensis and Phellodendron chinense , has been reported to possess the ability to protect experimental colitis through regulating innate and adaptive immune responses, intestinal barrier function and the gut microbiota (Lee et al, 2010; Yan et al, 2012; Kawano et al, 2015; Li et al, 2015, 2016; Lv Z. et al, 2015; Zhang et al, 2017; Cui et al, 2018; Jing et al, 2018; Liu et al, 2018). Among these reports, Yan et al (2012) revealed that oral administration of berberine (100 mg/kg of body weight in mice) significantly ameliorated DSS-induced intestinal injury and colitis associated with decreasing the disruption of barrier function and apoptosis of colon epithelium, thus inhibiting the proinflammatory cytokine TNF-α, IFN-γ, KC, and IL-17 production of colonic macrophages and promoting the apoptosis of colonic macrophages through down-regulating the activation of MAPK and NF-κB (Yan et al, 2012).…”
Section: Plant-based Alkaloids Against Ibdmentioning
confidence: 99%
“…Fecal transplantation from berberine-treated mice could relieve UC and regulate the Treg/Th17 balance. Further, using DSS-induced murine colitis, Jing et al (2018) investigated the effect of berberine on P-glycoprotein (P-gp), one of the most important proteins of the cell membrane that pumps harmful molecules out of the intestinal mucosa; the results revealed that berberine (10 and 40 mg/kg of body weight in mice, p.o.) could significantly ameliorate intestinal inflammation by enhancing P-gp expression, which is independent of nuclear factor erythroid 2-related factor 2 (Nrf2) activation.…”
Section: Plant-based Alkaloids Against Ibdmentioning
confidence: 99%
“…BBr potently suppressed the inflammatory response in macrophages by inhibiting nF-κB signaling via sirtuin-1-dependent mechanisms (20). administration of BBr can notably ameliorate disease severity and restore the mucosal barrier homeostasis of patients with uc (21), and upregulate P-glycoprotein via activation of nuclear factor erythroid 2-related factor 2-dependent mechanisms to improve symptoms in patients with uc (22). BBr also inhibits inflammatory responses as well as T helper cell (Th)1/Th7 differentiation to ameliorate 2,4,6-Trinitrobenzenesulfonic acid solution (TnBS)-induced iBd (23).…”
Section: Anti-inflammatory Mechanism Of Berberine On Lipopolysaccharimentioning
confidence: 99%